Teacher’s Talk in English Classroom Using Foreign Language Interaction (FLINT) System : A Case Study at SMP Negeri 1 Sungai Raya in Academic Year 2022/2023 - Jembaranita, Sarah; Clarry Sada; Eka Fajar Rahmani (Kirana Publisher (KNPub), 2024)
The researcher conducted the research to describe the teacher and student interaction during the teaching-learning process and to analyze the frequent FLINT categories by Moskowitz (1976). The participant in this research was an English female teacher taught in class VII F at SMP Negeri 1 Sungai Raya in the academic year 2022/2023. This research was a case study design that used qualitative method. The data was collected by observing the teacher and student interaction during the teaching-learning process. The researcher used the teacher talk video transcript in analyzing the FLINT categories. The result of the research showed that the teacher’s dominant language was Bahasa Indonesia. The teacher’s utterances in Bahasa Indonesia appeared 95 times during the teaching-learning process, which means the teacher used Bahasa Indonesia in English lessons. The teacher should be built good oral during the teaching-learning process, not only focus on delivering the material. The frequent categories used by the teacher were giving information and asking questions. Moreover, the rare category the teacher used was the student’s ideas. Through analyzing the FLINT system, teacher talk in the classroom was accessible in describing the dominant language performed by the teacher and analyzed frequent categories used by the teacher during the teaching-learning process.